Readiness of HIF Using the Single Pass RF Driver - Burke, Robert J.; Azim, Mansour Hadji; Helsley, Charles E.; Burke, Alexander T. (21st International Symposium on Heavy Ion Inertial Fusion. Autonomous Organization of Education “Nazarbayev University”, 2016)
Readiness for a concerted push to power production was the underlying theme from the inaugural HIF Workshop in 1976 through the review of ICF programs by DOE’s Energy Research and Advisory Board in 1979. Using John Lawson’s 1987 paper “Whither Heavy Ion Fusion?” [1] as a foil, this paper discusses the continuing vitality of the argument for HIF’s readiness against the backdrop that this vision is not in evidence today, having been occluded by political policies causing diversion of the HIF community into peripheral science that, although excellent, is in fact not required to complete the development of a HIF energy source...
Keywords: RF driver; beam; laser; Research Subject Categories::NATURAL SCIENCES::Physics::Elementary particle physics